2008
DOI: 10.1002/iub.48
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen is a modulator of vascular inflammation

Abstract: SummaryVascular inflammation underlies the pathogenesis of atherosclerosis. Atherosclerotic changes in the vasculature lead to conditions such as coronary artery disease and stroke, which are the major causes of morbidity and mortality worldwide. Epidemiological studies in premenopausal women suggest a beneficial role for estrogen in preventing vascular inflammation and consequent atherosclerosis. However, the benefits of estrogen are absent or even reversed in older postmenopausal subjects. The modulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 53 publications
1
63
0
2
Order By: Relevance
“…6 In animal models, oestrogen deficiency has been reported to lead to an increased level of tumour necrosis factor-alpha (TNF-a) and endothelin-1, leading to a possible proinflammatory state in the vasculature. 7 It is possible that the changes in oestrogen levels in our patient taking an AI led to changes in vasculature permeability and optic nerve swelling. Early recognition of this possible side effect may be crucial, as prompt discontinuation of the drug was associated with improvement of symptoms.…”
Section: Discussionmentioning
confidence: 93%
“…6 In animal models, oestrogen deficiency has been reported to lead to an increased level of tumour necrosis factor-alpha (TNF-a) and endothelin-1, leading to a possible proinflammatory state in the vasculature. 7 It is possible that the changes in oestrogen levels in our patient taking an AI led to changes in vasculature permeability and optic nerve swelling. Early recognition of this possible side effect may be crucial, as prompt discontinuation of the drug was associated with improvement of symptoms.…”
Section: Discussionmentioning
confidence: 93%
“…TNF-␣'s proinflammatory effects include upregulation of the adhesion molecules ICAM-1, VCAM-1, and E-selectin in endothelial cells, enhancing the recruitment of leukocytes (11,25,45). TNF-␣ also increases oxidative stress by activation of NADPH oxidase (9). iNOS, another proinflammatory gene, was increased markedly at the protein level only in the Late group.…”
Section: Discussionmentioning
confidence: 99%
“…These include modulation of vascular tone via both the endothelium-dependent mechanisms, as well as the mechanisms inherent to the VSMC (81). In addition, antioxidant, anti-inflammatory, and antiproliferative pathways modulated by estrogen protect against vessel injury from exposure to the vascular risk factors (16). This has been a subject of recent reviews (as indicated above), and will not be covered in detail here.…”
Section: Vascular Changes In Aging Womenmentioning
confidence: 99%